2014
DOI: 10.4338/aci-2014-08-ra-0067
|View full text |Cite
|
Sign up to set email alerts
|

User-Centered Design and Usability Testing of an Innovative Health-Related Quality of Life Module

Abstract: SummaryObjectives: Various computerized health risk appraisals (HRAs) are available, but few of them assess health-related quality of life (HRQoL) in a goal-directed framework. This study describes the user-centered development and usability testing of an innovative HRQoL module that extends a validated HRA tool in primary care settings. Methods: Systematic user-centered design, usability testing, and qualitative methods were used to develop the HRQoL module in primary care practices. Twenty two patients and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Our past research aimed to develop a 3-step, goal-directed care delivery model 3, 9, 10 that includes patient and practice preparation for wellness visits (“Ready” step), HRA-based goal setting and health planning during wellness visits (“Set” step) and systematic follow-up to support goal attainment (“Go” step). Although we have learned much from these studies about the first and third steps, our understanding remained limited about the conversation that occurred when the HRA report was introduced and how these conversations could be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Our past research aimed to develop a 3-step, goal-directed care delivery model 3, 9, 10 that includes patient and practice preparation for wellness visits (“Ready” step), HRA-based goal setting and health planning during wellness visits (“Set” step) and systematic follow-up to support goal attainment (“Go” step). Although we have learned much from these studies about the first and third steps, our understanding remained limited about the conversation that occurred when the HRA report was introduced and how these conversations could be improved.…”
Section: Discussionmentioning
confidence: 99%
“…User acceptance was a frequently discussed theme in e-prescribing systems [51] and two papers found that user interface design has a major impact on e-prescribing [52,53]. Related to these findings were papers on usability of drug alerts [54], work flow analysis in diabetes [55], and user centered design of tools to document falls [56] or quality of life [57].…”
Section: Major Topics Discussed In Acimentioning
confidence: 99%
“…The desired usability expectations and user experience goals need not be compromised if users’ interactions with the systems are optimized (Asuquo et al, 2009). The systematic application of user-centered design and human factors principles in technology development and testing may greatly enhance the usability and clinical utility of health information systems (Nagykaldi et al, 2014). The results of usability testing might have a substantial influence on patient safety and general healthcare outcomes (Carayon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%